2012
DOI: 10.12659/msm.882458
|View full text |Cite
|
Sign up to set email alerts
|

Determination of PKC isoform-specific protein expression in pulmonary arteries of rats with chronic hypoxia-induced pulmonary hypertension

Abstract: SummaryBackgroundEvidence indicates that protein kinase C (PKC) plays a pivotal role in hypoxia-induced pulmonary hypertension (PH), but PKC isoform-specific protein expression in pulmonary arteries and their involvement in hypoxia-induced PH are unclear.Material/MethodsMale SD rats (200–250 g) were exposed to normobaric hypoxia (10% oxygen) for 1, 3, 7, 14 and 21 d (days) to induce PH. PKC isoform-specific membrane translocation and protein expression in pulmonary arteries were determined by using Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The authors suggest that the attack of reactive oxygen species during the oxidative stress primarily affects the saturation level of fatty acyl chains and the phospholipid structure. 7,8 In contrast to systemic hypertension that is diagnosed on the basis of simple systemic blood pressure measurements, the diagnosis of PAH requires a combination of tests, e.g. This approach included a method of identification and quantification of several serum protein parameters from one ATR FTIR spectrum such as the content of total albumin, globulin and immunoglobulin as well as their relative contribution to the overall protein composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggest that the attack of reactive oxygen species during the oxidative stress primarily affects the saturation level of fatty acyl chains and the phospholipid structure. 7,8 In contrast to systemic hypertension that is diagnosed on the basis of simple systemic blood pressure measurements, the diagnosis of PAH requires a combination of tests, e.g. This approach included a method of identification and quantification of several serum protein parameters from one ATR FTIR spectrum such as the content of total albumin, globulin and immunoglobulin as well as their relative contribution to the overall protein composition.…”
Section: Introductionmentioning
confidence: 99%
“…PAH is a chronic progressive disease of the pulmonary vasculature, characterized by an elevated pulmonary arterial pressure leading to right ventricular failure. 7,8 In contrast to systemic hypertension that is diagnosed on the basis of simple systemic blood pressure measurements, the diagnosis of PAH requires a combination of tests, e.g. functional assessment, exercise tolerance, laboratory tests, magnetic resonance imaging, and echocardiography to support right heart hypertrophy or failure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that androgens play a critical role in cardiovascular disease [ 20 ] and are associated with pulmonary arterial hypertension [ 21 ], and AR had been identified in the right and left ventricles [ 22 ]. The changes in membrane translocation and protein expression of cPKC α , β I, β II, and nPKC δ are involved in the development of hypoxia-induced rat pulmonary hypertension [ 23 ]. An organized thrombus in major pulmonary arteries is typically in association with other diseases, such as lung cancer [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Shi et al [46 ]demonstrated decreased PKCα expression in the pulmonary arteries of rats with hypoxia-induced pulmonary hypertension. Moreover, increased TP receptor density has been observed in the right ventricular tissue of PAH patients [47].…”
Section: Discussionmentioning
confidence: 99%